Wakaf Uang dalam Perspektif Hukum Islam - Nanang Qosim (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2018)
Waqf is a wakif legal act to separate and / or hand over some of his possessions to be used forever or for a certain period in accordance with his interests for the purposes of worship and / or general welfare according to the Shari'ah. Wakif is a Party who injects his property.Nazhir is a Party that receives wakaf's property from wakif to be managed and developed in accordance with its intended.PPAIW is the authorized official set by the Minister to make the Deed of Wakaf Pledge. Keywords: Endowment and Money